2021
DOI: 10.1037/law0000323
|View full text |Cite
|
Sign up to set email alerts
|

Do exonerees face housing discrimination? An email-based field experiment and content analysis.

Abstract: Two studies examined housing discrimination against exonerees. In Study 1, we sent 1,203 emails inquiring about active apartment listings, each of which ostensibly came from an ex-offender, an exoneree, or a person with no criminal history. Compared to the control condition (51%), both ex-offenders (40%) and exonerees (regardless of whether they self-described as "exonerated," "wrongly convicted," or "innocent"; 34-41%) were less likely to receive any response. Moreover, a content analysis suggested that repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 61 publications
(104 reference statements)
6
15
0
Order By: Relevance
“…Prior research has demonstrated housing discrimination toward individuals with a criminal history (e.g., Evans & Porter, 2015;Kukucka et al, 2021) and individuals belonging to racial minority groups (e.g., Carpusor & Loges, 2006;Hanson et al, 2011). The current findings extend this research by analyzing landlords' initial written correspondence with potential renters.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Prior research has demonstrated housing discrimination toward individuals with a criminal history (e.g., Evans & Porter, 2015;Kukucka et al, 2021) and individuals belonging to racial minority groups (e.g., Carpusor & Loges, 2006;Hanson et al, 2011). The current findings extend this research by analyzing landlords' initial written correspondence with potential renters.…”
Section: Discussionsupporting
confidence: 63%
“…In interviews with 115 wrongfully convicted individuals, approximately half reported that they were dependent upon families, friends -or even lawyers -for housing support (Roberts & Stanton, 2007). In a recent study by Kukucka et al (2021), researchers sent rental email inquiries across the U.S. from individuals who were supposedly either convicted, wrongfully convicted (selfdescribed as "exonerated," "wrongfully convicted," or "innocent") or had no criminal history. Results revealed that both convicted and wrongfully convicted individuals (regardless of label) were less likely to receive a response from landlords than those without a criminal history.…”
Section: Housing Difficultiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have gauged public attitudes toward wrongly convicted individuals, generally finding that exonerees-despite their innocence-are negatively stereotyped and stigmatized similarly to actual offenders (e.g., Blandisi et al, 2015;Clow & Leach, 2015a;Thompson et al, 2012; for an exception, see Tudor-Owen et al, 2019; for a review, see Faison & Smalarz, 2019). Accordingly, field experiments have found that exonerees face employment discrimination (Clow, 2017;Kukucka et al, 2020) and housing discrimination (Kukucka et al, 2021;Zannella et al, 2020) comparable to offenders, which present considerable barriers to reintegration. To explain such findings, researchers have speculated that the public may doubt exonerees' innocence (perhaps to preserve their belief in a just world; Hafer & Bègue, 2005;Scherr et al, 2018a) and/or believe that exonerees have been corrupted by their prison experience (i.e., stigma-by-association; Clow et al, 2012;Goffman, 1963).…”
Section: Introductionmentioning
confidence: 99%